Cultural experiences of student and new‐graduate dietitians in the Gomeroi gaaynggal ArtsHealth program: a quality assurance project. (20th April 2016) - Rae, Kym; Bohringer, Emma; Ashman, Amy; Brown, Leanne; Collins, Clare
Abstract : Issue addressed: Undergraduate dietetic students are required to demonstrate cultural awareness and culturally respectful communication to meet national competencies, but exposure to practical experiences may be limited. The Gomeroi gaaynggal ArtsHealth Centre was established in 2009 after community consultation with the Indigenous community in Tamworth, New South Wales. The Centre provides a safe and welcoming space where women can create art while discussing health issues with visiting health professionals and students. The present study aimed to evaluate the cultural experiences of student and new‐graduate dietitians visiting an Aboriginal ArtsHealth centre through a quality assurance project. Methods: Six student and new‐graduate dietitians were invited to provide feedback on their experiences for this report. A generic inductive approach was used for qualitative data analysis. Results: Key qualitative themes of 'building rapport' and 'developing cultural understanding' were identified. Four of the participants interviewed felt they gained a deeper understanding of the context around health disparity for Indigenous Australians through their experiences. Key ways to build rapport with community members were identified. Conclusions: Results suggest that first‐hand experiences working in an Aboriginal ArtsHealth centre are effective in building cultural competency skills for student and new‐graduate dietitians. These experiences could be better supported through improved preparation for the cultural setting, and ongoing monitoring of participant experiences is recommended. So what?: The authors encourage undergraduate dietetic programs and students to seek out opportunities for further development of cultural awareness through increased practical experiences working with Indigenous communities. Abstract : Dietitians have roles to play in optimising nutrition for Indigenous Australians, but exposure to practical experience may be limited. This quality assurance project evaluated the experiences of student and new‐graduate dietitians at an Aboriginal ArtsHealth centre, and identified key themes of 'building rapport' and 'developing cultural understanding'. Dietetic students are encouraged to seek out opportunities for development of cultural awareness by working with Indigenous communities where possible.